Prebiotic Activity of Pectin from Ambon Lumut Banana (Musa acuminata AAA) Peel - Bertha Rusdi; Onoy Rohaeni; Miski A. Khairinisa; Umi Yuniarni (Pharmacology and Clinical Pharmacy Research, 2022)
Banana peel is an agricultural waste that contains pectin. Ambon lumut banana (Musa acuminata AAA) is often consumed in Indonesia, but its peel is rarely utilized thus the availability of Ambon lumut banana peel in Indonesia is high. Pectin selectively increases beneficial gut bacteria, and this is commonly known as prebiotic. This study aims to evaluate the prebiotic activity of Ambon lumut banana peel by observing the growth of a beneficial gut bacteria, Lactobacillus acidophilus, and pathogen enteric bacteria, Escherichia coli, in media (MRSB) enriched with the pectin. The result showed that 1% of Ambon lumut banana peel pectin significantly increased the number of L. acidophilus and decreased the number of E. coli compared to bacteria culture without carbon source (glucose-free MRSB) and bacteria culture with glucose as carbon source. The prebiotic index of Ambon lumut banana peel pectin was 0.53. In addition to that, the short chain fatty acid (SCFA) which is beneficial metabolite of L. acidophilus for human health was also measured using HPLC.  The HPLC analysis results showed that L. acidophilus culture enriched with pectin contains SCFA, including acetic acid, butyric acid, and propionic acid at the concentration of 10.22 µg/mL, 5.38 µg/mL and 0.55 µg/mL respectively.